Buxus papillosa C.K. Schneid.: A comprehensive review on traditional uses, botany, phytochemistry, pharmacology, and toxicology. (November 2022) - Saleem, Hammad; Khurshid, Umair; Anwar, Sirajudheen; Tousif, Muhammad Imran; Mahomoodally, Mohamad Fawzi; Ahemad, Nafees
Abstract: Buxus papillosa C.K. Schneid, (common name: Shamshad) is one of the most common plants of the family Buxaceae, having various folklore uses to treat common ailments. Despite the prospective health benefits, this plant still it is not yet well-recognized in the modern medicinal system. The present review article is directed to furnish a systematic outline of the botanical aspects, folklore/traditional utilization, secondary metabolites composition, pharmacological/biological effects, and toxicological parameters of B. papillosa . The literature was searched using electronic databases as per Science Direct, Google Scholar, PubMed, and Scopus with the search terms " Buxus papillosa " and "traditional uses", "pharmacological activities", "chemical composition", and "toxicity" to assemble all accessible data involving this plant. The plant was found to have reported traditional uses, including skin problems, toothache, malaria, rheumatism, anti-diarrheal, and cardiotonic agent. Regarding phytochemistry, about 64 different phytochemical compounds belonging to triterpenoid and alkaloid steroidal classes were described to be isolated from B. papillosa different parts. Likewise, 36 different secondary metabolites have also been reported to be tentatively detected by UHPLC-MS analysis, and most of these were phenolic, flavonoid, and saponin classes of phytochemicals. Moreover, different crude extracts and/or isolated compounds of this plant have also been tested for different pharmacological effects, including enzyme inhibition, antioxidant, antispasmodic, anti-microbial, and anthelmintic activities. Likewise, the toxicity potential of the plant against the selected human carcinoma cell lines is also discussed. Furthermore, the current review also presented a critical evaluation and future recommendations regarding these studies. The data presented in this review will be very beneficial for future studies on this plant in order to design lead bioactive compounds. Highlights: Buxus papillosa C.K. Schneid, (common name: Shamshad) is well known for its various folklore uses. Current review covers traditional uses, photochemistry, pharmacological effects and toxicity studies on Buxus papillosa. The isolation of the specific class of secondary metabolites indicate this plant is a rich source of steroidal and triterpenoidal alkaloids.